PENGARUH KOMPENSASI, UKURAN PERUSAHAAN, USIA PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BEI PERIODE 2012-2015 - YUMIASIH, LILIS (Jurnal Ilmu Manajemen (JIM), 2017)
Firm value is the most important concept in a firm. Firm value can be seen from market value of a firm by overall, because the higher the firm value, the higher the wealth of shareholders. This study has purpose to know the influence of compensation, firm size, firm age, and leverage towards firm value. This study used secondary data that covers 14 companies in agriculture sector that registered in BEI period 2012-2015 by using purposive sampling technique. The result showed that firm age influences firm value. While compensation and firm age do not influence firm value because the higher or lower the compensation given by firm would not be noticed by potential investors. Leverage variable also does not influence firm value which means that the higher or lower firm’s debt would not be noticed by investors because investors see how firm’s management use their fund effectively and efficiently to achieve added-value for firm value. The implication of this study is for the next researcher to be able to test independent variable that doesn’t influence firm value by using more precise different proxies for every variable to provide the more accurate result. The next test can also use different sample. Keywords: Compensation, Firm Size, Firm Age, Leverage, Firm Value